Hands-On Deep Learning for Finance : Implement deep learning techniques and algorithms to create powerful trading strategies /: Implement deep learning techniques and algorithms to create powerful trading strategies. (2020) - Troiano, Luigi; Bhandari, Arjun; Villa, Elena Mejuto
No abstract available